2012
DOI: 10.1007/s10654-012-9729-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating vitamin D, calcium and risk of cerebrovascular disease: a systematic review and meta-analysis

Abstract: Available literature suggests that both vitamin D and calcium may be associated with a wide range of non-skeletal outcomes. However, epidemiological evidence supporting their individual associations with incident cerebrovascular disease is scarce. We conducted a systematic review and meta-analysis of prospective cohort studies, published before February 2012 and sought from MEDLINE, EMBASE, BIOSIS and the Science Citation Index databases, and reported cerebrovascular disease (defined as any fatal or non-fatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 40 publications
1
41
0
2
Order By: Relevance
“…A recent metaanalysis of prospective observational studies revealed an inverse relationship between levels of 25(OH)D 3 and risk of CVD, including coronary heart disease, stroke, and total CVD mortality (473). These increased risks for coronary heart disease and ischemic stroke or cerebrovascular disease for individuals with the lowest 25(OH)D 3 levels were also observed in other meta-analyses (60,61,82).…”
Section: Vitamin D: Pleiotropic Effectsmentioning
confidence: 78%
“…A recent metaanalysis of prospective observational studies revealed an inverse relationship between levels of 25(OH)D 3 and risk of CVD, including coronary heart disease, stroke, and total CVD mortality (473). These increased risks for coronary heart disease and ischemic stroke or cerebrovascular disease for individuals with the lowest 25(OH)D 3 levels were also observed in other meta-analyses (60,61,82).…”
Section: Vitamin D: Pleiotropic Effectsmentioning
confidence: 78%
“…The study reported positive association of high levels of 25(OH)D (>89 ng/mL) with incidence of heart diseases [99]. Risk of cerebrovascular disease [100] and stroke [101] was significantly lower in subjects with high 25(OH) D levels compared to those with insufficient vitamin D status. Similar results were demonstrated in 40,000 individuals [102], coronary angiography and diabetic patients [103,104] and in 203 individuals with subclinical carotid atherosclerosis [105].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Latitude, season, cultural norms, religious practices, low awareness, low knowledge/health literacy, indoor lifestyles, urban living, skin pigmentation, malnutrition, diet, co-morbidities like tuberculosis, and drugs may contribute to vitamin D deficiency especially in the in the developing world, moreover, blacks tend to have lower levels of 25(OH)D compared to whites [2,3]. It has been widely demonstrated that Vitamin D is also involved in different non-skeletal functions, including hypertension, diabetes, multiple sclerosis, Alzheimer's disease, Parkinson's disease, and Stroke [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%